OPTIMALISASI PROGRAM KALIMASADA MELALUI KEGIATAN “JEBOL ANDUK” SEBAGAI UPAYA MASYARAKAT TERTIB ADMINDUK KELURAHAN KEBONSARI - Evinda Fenny Wulandari; Muhammad Roisul Basyar (Jurnal Ilmu Administrasi Negara, 2023)
Population administration is a series of activities related to population data. Every citizen is obliged to have population data and to report all important events that occur. The Kalimasada (Adminduk Conscious Community Environmental Area) programs is one of the programs initiated by the Surabaya City Government to address the problem of orderly administration of population administration in Surabaya. This type of research uses a qualitative approach with the observation method carried out to be able to identify obstacles to optimizing the Kalimasada program in Kebonsari Village. Based on the results of the discussion, it was found that there were several inhibiting factors that caused the community to be disorderly adminduk. Based on these problems, efforts were made in the form of the “Jebol Anduk” service or the adminduk ball pickup service by going directly to residencts homes. The implementation of this efforts is expected to provide a solution to the problem of orderly administration of population in the Kebonsari Village